Clinical Team Response to the Impact of COVID-19 on Diabetes Self-Management: Findings From a Qualitative Study - Hale, Lily; Cameron, Thomas C.; Donahue, Katrina E.; Vu, Maihan B.; Leeman, Jennifer; Johnson, Asia; Richman, Erica; Rees, Jennifer; Young, Laura (Frontiers in Clinical Diabetes and Healthcare, 2022)
The aims of this study were to explore providers’ perceptions of how COVID-19 affected patients’ psychological wellbeing and diabetes self-care and discover how providers responded to sustain and improve patients’ psychological health and diabetes management during the pandemic. Twenty-four semi-structured interviews were completed with primary care providers (n=14) and endocrine specialty clinicians (n=10) across sixteen clinics in North Carolina. Interview topics included: (1) current glucose monitoring approaches and diabetes management strategies for people with diabetes (2) barriers and unintended consequences encountered with respect to diabetes self-management, and (3) innovative strategies developed to overcome barriers. Interview transcripts were coded using qualitative analysis software and analyzed to identify cross-cutting themes and differences between participants. Primary care providers and endocrine specialty clinicians reported that people with diabetes experienced increased mental health symptoms, increased financial challenges and positive and negative changes in self-care routines due to COVID-19. To offer support, primary care providers and endocrine specialty providers focused discussions on lifestyle management and utilized telemedicine to connect with patients. Additionally, endocrine specialty clinicians helped patients access financial assistance programs. Findings indicate that people with diabetes experienced unique challenges to self-management during the pandemic and providers responded with targeted support strategies. Future research should explore the effectiveness of these provider interventions as the pandemic continues to evolve.